Pengaruh Sistem Pembelajaran Boarding Shcool (Asrama) Dan Program Pembinaan Agama Islam (PPAI) Terhadap Kecerdasan Spiritual Mahasiswa Muslim Di Asrama Green Dormitory Universitas Malahayati Bandar Lampung: Pembelajaran Boarding Shcool - Sutikno (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2020)
Spiritual intelligence is one of important abilities that must be achieved by people, the objective of this study was to identify the effect of boarding learning and Islamic Religious Development Program (Program Pembinaan Agama Islam/PPAI) applied at Malahayati University Bandar Lampung towards the spiritual intelligence of the students. The method used in this study was survey technique continued with Path Analysis. The study was conducted at Student Dormitory (Green Dormitory) of Malahayati University in Bandar Lampung in 2019-2020 academic year, The data collection was done on 100 students through questionaires with likers scale and data processing was through SPSS version 16. Based on the first hypothesis test, it shows that there were direct and significant effects of boarding learning towards spiritual intelligence of the students. The percentage indicated that 14% of students’ spiritual intelligence is influenced by boarding learning sistem. The second hypothesis test revealed that there were direct and significant effects of boarding learning towards spiritual intelligence of the students indicated by 19.2% improvement. It means that the spiritual intelligence of Muslim students at Malahayati University was influenced by Islamic Religious Development Program (Program Pembinaan Agama Islam/PPAI). The third hypothesis test, done simultaneously, found that there was effect of boarding learning and Islamic Religious Development Program (Program Pembinaan Agama Islam/PPAI) towards spiritual intelligence of the students at Green Dormitory of Malahayati University. The effect was 21.5% for the spiritual intelligence improvement on the students after following Islamic Religious Development Program (Program Pembinaan Agama Islam/PPAI during residency at Green Dormitory of Malahayati University.